Pengembangan E-Modul dengan Pendekatan SETS untuk Meningkatkan Literasi Sains Siswa SMP/MTs pada Materi Pemanasan Global: Systematic Literature Review (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2023)
This research was conducted in order to analyze literature related to the development of E-Modules with the SETS approach to increase students' scientific literacy. The purpose of this research is to select articles that are feasible for analysis related to the development of E-Modules with the SETS approach to increase students' scientific literacy. The benefit of this research is to facilitate researchers in obtaining proper literature to be analyzed related to the title of the research to be conducted by researchers. The method of this study is using the Systematic Literature Review (SLR) method, which is a method that has steps consisting of identification, screening, eligibility and inclusion. The conclusion of this study is the systematic literature review (SLR) method which aims to facilitate researchers in conducting research whose research results are based on the results of literature analysis that have been selected in stages through several systematic procedures. Based on the results of the systematic literature review (SLR) method that has been carried out by researchers, 21 literatures are feasible for analysis. The results of the systematic literature review (SLR) method that has been carried out to select some literature, the total amount of literature that is issued or not feasible for analysis is 1,597 literature.